Operational Standard for Eye Acupuncture with Acupuncture Rehabilitation Therapy of Traditional Chinese Medicine Rehabilitation Techniques - Working Group of Operational Standard for Eye Acupuncture with Acupuncture Rehabilitation Therapy of Traditional Chinese Medicine Rehabilitation Techniques; SHAO Yan; CUI Cong; KANG Jian; ZHAO Xitong; YU Lihua; YANG Sen; SUN Mengjia; WANG Chenyang; WANG Xingyang; WANG Pengqin (康复学报)
Eye acupuncture with acupuncture rehabilitation therapy refers to the organic combination of eye acupuncture therapy and modern rehabilitation technology. According to the different functional disorders of rehabilitation objects, the corresponding acupoints of "Eight Areas and Thirteen Points of Eye Acupuncture" were selected to bury the needles, and various rehabilitation training were carried out simultaneously during the needle retention period. The main purpose of establishing the operational standard for eye acupuncture with acupuncture rehabilitation therapy is to standardize management and guide the professionals and technical personnel of traditional Chinese medicine to correctly use the eye acupuncture and acupuncture rehabilitation therapy for rehabilitation treatment. This standard includes the technical scope of eye acupuncture and acupuncture rehabilitation therapy, normative references, terminology and definitions (eye acupuncture physical therapy, eye acupuncture occupational therapy, eye acupuncture speech training, eye acupuncture cognitive rehabilitation training, eye acupuncture pain rehabilitation techniques), operating procedures and requirements (selection of eye acupuncture needles, acupoint selection principle, body position selection, environmental requirements and operation methods, etc.), main indications, contraindications, precautions and other aspects. This operational standard could be applied to guide the professionals and technical personnel of traditional Chinese medicine in hospitals at all levels and medical and health care institutions to carry out eye acupuncture with acupuncture rehabilitation therapy, with wide generality and effectiveness.